Os efeitos da licença maternidade sobre o salário e o emprego da mulher no Brasil - Sandro Sacchet de Carvalho; Sergio Firpo; Gustavo Gonzaga (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2006)
– This paper aims to estimate the effects of maternity leave legislation in women's wages and employment in Brazil. We analyze the impact of an increase in the leave period, which was raised from 12 weeks to 120 days, as prescribed by the Federal Constitution of 1998. According to the theoretical literature, the effect of the legislation is ambiguous. One should expect that the leave would have negative effects on labor demand to the extent that it raises labor costs. On the other hand, the legislation is expected to increase labor supply and can have positive effects on wages if it avoids that women leave the labor market each time they have a child, therefore increasing the firm-specific human capital of these workers. We use a simple difference-indifferences methodology applied to data from Pesquisa Mensal de Emprego between 1986 and 1991. We compare the changes in wages and employment between the periods before and after the 1988 Constitution of women in fertile ages (our treatment group) with those of two control groups: men at the same ages and women in non-fertile ages. The results show that the leave increase had no significant impact on wages. We also find no signs that the leave increase raised women's retention in the labor market, even in the case of the more educated female workers. The results also show insignificant impact in women's employment.
Keywords: J7; 330; licença maternidade; salário da mulher; emprego da mulher; Mutterschutz; Weibliche Arbeitskräfte; Fraueneinkommen; Brasilien